Time frequency analysis for wireless channel characterization / Zaiton Sharif - Sharif, Zaiton (Institute of Graduate Studies, UiTM, 2016)
The ability to accurately characterize the wireless communication channel is essential for testing and designing any wireless communication systems. It fulfills the demand for a better quality of communication service in terms of higher bits rate and the use of spread spectrum technology. One of the challenges for wireless channel characterization is the need to demonstrate an appropriate method to characterize the wireless channel hence, effective channel mitigation technique can be developed to minimize deleterious effect arise from the channel namely the short terms variations due to multipath fading. This propagation environment affects the transmitted signal in terms of scattering, diffraction and reflection as it traveled towards the receiver causing the signals to be received distorted or interfered. Therefore, the central issue in this thesis is to determine appropriate techniques to characterize such a channel. A statistical property was adopted to represent properties of the channel which was categorized under wide sense stationary uncorrelated scattering (WSSUS) conditions. In achieving research objectives, four methods are employed namely Cross Correlation Function (CCF), Cross Ambiguity Function (CAF), Cross Wigner Ville Distribution (CWVD) and Cross S Transform (CST)…